Robert T. Tally Jr. (ed.), Spatial Literary Studies: Interdisciplinary Approaches to Space, Geography, and the Imagination - Corrado Confalonieri (Università degli Studi di Cagliari, 2021)
Recensione del volume di Robert T. Tally Spatial Literary Studies: Interdisciplinary Approaches to Space, Geography, and the Imagination.